Proses Penyusunan Rencana Tata Ruang dalam Kaitan Kelestarian Fungsi Lingkungan Hidup - Nina Mirantie Wirasaputri (Universitas Syiah Kuala, 2014)
The research on the arrangement process of spatial planning to keep the environmental function sustainability in Central Java Province is purposed at exploring (1) whether the process of the arrangement of spatial planning has been in accordance with the rules? (2) how is the position of the planning on the sustainability of the environment? (3) how is the participation of people in the arrangement in Central Java Province? This is juridical empirical research by applying secondary and primary data. The data then analysed descriptive qualitatively. The research shows the planning of Central Java between 2003-2018 is not optimal yet as demanded by the rules. It results from lack of attention on integrated principle, sustaionability, transparency and legal protection. Apart from that the society also lack of participation in the planning. The Process of Spatial Planning Arrangement in Relation to Environmental Function Sustainability